5x-3x+12=120-6x+16

Simple and best practice solution for 5x-3x+12=120-6x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3x+12=120-6x+16 equation:


Simplifying
5x + -3x + 12 = 120 + -6x + 16

Reorder the terms:
12 + 5x + -3x = 120 + -6x + 16

Combine like terms: 5x + -3x = 2x
12 + 2x = 120 + -6x + 16

Reorder the terms:
12 + 2x = 120 + 16 + -6x

Combine like terms: 120 + 16 = 136
12 + 2x = 136 + -6x

Solving
12 + 2x = 136 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
12 + 2x + 6x = 136 + -6x + 6x

Combine like terms: 2x + 6x = 8x
12 + 8x = 136 + -6x + 6x

Combine like terms: -6x + 6x = 0
12 + 8x = 136 + 0
12 + 8x = 136

Add '-12' to each side of the equation.
12 + -12 + 8x = 136 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = 136 + -12
8x = 136 + -12

Combine like terms: 136 + -12 = 124
8x = 124

Divide each side by '8'.
x = 15.5

Simplifying
x = 15.5

See similar equations:

| 6i+5i(i-2)=0 | | 2x+52=x | | -35+4x=33 | | (x^2+y)dx+(y^3+x)dy=0 | | 1200=8*2.85*t | | 84-25x=26-x+3 | | 6i+5i(1-2)=0 | | 84+11x=26-x+3 | | 17+10x=97 | | 15*(-24)+50= | | I=6*315*5 | | 30+.05x=0.2x | | 7x+3-8x=12-7x-6 | | 8x+74=210 | | 3x=10x^2-2 | | -53+8x=43 | | 5x-6=42 | | 26.98*z=1.53 | | 18500=7*3.5*t | | 1+x/13=6 | | 6x^3+2x=0 | | 216x^2-144x-22=6x^2+54 | | x=5/y | | 2+x/11=8 | | x^2-8+16= | | 7x=97 | | 7x+16=8x+10 | | 2x-5=5(x-1)-3x | | 1277=4*r*3 | | y(y)-y=0 | | y=180+45x | | -8(5-5k)=-40-6k |

Equations solver categories